Motivation in learning the Arabic language among Chinese students at a University in the Hebei Province, China - Chang, Weiwei (2019)
The Arabic language is one of the languages that are increasingly gaining the attention of Chinese students in China. Therefore, this study is aimed at researching the motivations of learning the Arabic language among Chinese students in terms of integrative and instrumental motivations. The researcher adopted the qualitative approach through field research. A total of nine (9) Chinese students currently studying the Arabic language at the Faculty of European Languages in the University of Foreign Languages in the Hebei Province in China, participated in this study. Data was collected through interviews, and subsequently analysed based on the Gardner theory. The findings of the research revealed that integrative motivation consists of three (3) categories: linguistic motivation, cultural motivation, and motivation resulting from the pleasures derived from the scenic views of the Arab countries. Integrative linguistic motivation is divided into six (6) sub-motivations which are the strong interest to learn multiple foreign languages; the strong interest to speak the Arabic language with Arabs; the strong interest to feel more competent in the ability the students have acquired in speaking the language; the strong interest to learn the Arabic language because the language specialisation was their personal choice; the strong interest to acquaint themselves with Arabic writings; and lastly, the strong interest to write in the Arabic language. Meanwhile, cultural motivation arose as the result of their interest to understand the cultural traditions of the Arab community, especially in the aspect of Arab cuisine. The third integrative motivation that results from the pleasures derived from the scenic views of the Arab countries is transpired by the students’ hobby in photography. Meanwhile, instrumental motivation is divided into five (5) categories, namely linguistic motivation, religious motivation, scientific motivation, practical motivation, and influence motivation. Linguistic instrumental motivation consists of two (2) sub-motivations. The first sub-motivation is that the Arabic language is used in the United Nations, while the second explains that the pronunciation of the Arabic language is similar to that of the mother tongue of the students, which is the Uighur language. The religious instrumental motivation is also divided into two (2) sub-motivations, which are the facts that the students are Muslims, and that they need to travel to Mecca to perform the Hajj. The scientific instrumental motivation, on the other hand, is divided into six (6) sub-motivations: that the Arabic language is a useful communication tool for the future; the importance of the Arabic language for furthering one’s studies in Arab countries; the encouragement from parents following the scientific advantages of the Arabic language itself; the use of the Arabic language for traveling to Arab countries; government encouragement; and also the self-reliance aspect. Meanwhile, the practical instrumental motivation entails the beliefs of the students that job opportunities in the Arabic language domain will be vast in the future; their desire to practise the language at work; and commercial interaction with Arab traders. Among the fields of professions mentioned by the respondents in the interviews are teaching, translation, and trade. The last part on the analysis of the instrumental motivation that was established by the researcher is the influence motivation. This influence instrumental motivation is divided into five (5) sub-motivations: the influence of Muslims living around the students; the influence of Arabic language programmes; the influence of famous figures like He Jiong who is fluent in the Arabic language; the benefits of reading Arabic novels; and also the influence of Arabic language teachers.